1999
DOI: 10.1152/ajpendo.1999.276.6.e1049
|View full text |Cite
|
Sign up to set email alerts
|

Effect of GIP and GLP-1 antagonists on insulin release in the rat

Abstract: Glucose-dependent insulinotropic polypeptide (GIP) and glucagon-like peptide 1 (GLP-1) are potent insulinotropic peptides released from the small intestine. To examine their relative contribution to postprandial insulin release, a specific GIP antagonist (ANTGIP) and a GLP-1 antagonist, exendin-(9—39)-NH2, were infused into rats after an intragastric glucose meal. In control rats, plasma glucose and insulin levels rose gradually during the first 20 min and then decreased. Exendin-(9—39)-NH2 administration inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
53
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(61 citation statements)
references
References 27 publications
8
53
0
Order By: Relevance
“…6. These actions include effects on hexose transport in the intestine (Tseng et al 1999) or actions on liver, muscle or adipose tissue (O'Harte et al 1998, Yip & Wolfe 2000, Rudovich et al 2004). However, it may be possible that the reduction in basal plasma glucose concentrations by daily GIP(3-42) treatment led to reduced glucose toxicity in these animals and thus contributed to the improvement of their diabetic status.…”
Section: Discussionmentioning
confidence: 99%
“…6. These actions include effects on hexose transport in the intestine (Tseng et al 1999) or actions on liver, muscle or adipose tissue (O'Harte et al 1998, Yip & Wolfe 2000, Rudovich et al 2004). However, it may be possible that the reduction in basal plasma glucose concentrations by daily GIP(3-42) treatment led to reduced glucose toxicity in these animals and thus contributed to the improvement of their diabetic status.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies where exendin amide was administered to rats, postprandial insulin release was reduced by 50-70% [16,18]. Other studies concluded that the incretin effects of GIP and GLP-1 account for greater than 50% of meal-induced insulin release, with the insulin response decreased by 72% following administration of the GIP receptor-antagonist, GIP(7-30)-NH 2 (ANTGIP), to chow-fed rats [44,45]. These values are broadly in line with our study.…”
Section: Discussionmentioning
confidence: 99%
“…injection (n=8) of saline (0.9% (w/v) NaCl; control), (Pro 3 )GIP (25 nmol/kg body weight), exendin(9-39)amide (25 nmol/kg body weight) or a combination of both peptides (each at 25 nmol/kg body weight). These doses will result in high concentrations of antagonist (µmol/l) relative to endogenous GIP or GLP-1 (pmol/l range) [46], and have been shown in other studies to abolish oral glucose or peptide-induced insulin increase [26,45]. Following injection (8 ml/kg body weight; final volume), the mice were allowed to re-feed for 15 min, and the food intake monitored.…”
Section: Effects Of (Pro3)gip and Exendin(9-39)amide On Plasma Glucosmentioning
confidence: 99%
“…Analyses based on the FDA Adverse Event Reporting System (FAERS) showed that incretinmimetic drugs are linked with increased incidence of pancreatitis and pancreatic cancer compared with other anti-diabetic drugs [160][161][162] [161]. Based on this evidence, FDA investigates reports of possible increased risk of pancreatitis and pre-cancerous findings of the pancreas from incretin-mimetic drugs [71].…”
Section: Cancermentioning
confidence: 99%